Mapping protein structural changes by quantitative cross-linking - Kukacka, Zdenek; Rosulek, Michal; Strohalm, Martin; Kavan, Daniel; Novak, Petr (Methods (San Diego, Calif.), 2015)
Chemical cross-linking is a promising technology for protein tertiary structure determination. Though the data has low spatial resolution, it is possible to obtain it at physiological conditions on proteins that are not amenable to standard high resolution techniques such as X-ray, NMR analysis and cryo-EM. Here we demonstrate the utilization of isotopically labeled chemical cross-linking to visualize protein conformation rearrangements. Since calmodulin exists in two distinct conformations (calcium-free and calcium-containing forms), we selected this protein for testing the potential and the limits of a new technique. After cross-linking of both calmodulin forms, the calcium-free and calcium-containing forms were mixed together and digested under different conditions and the products of proteolysis were monitored using high resolution mass spectrometry. Finally, the ratios of heavy/light cross-links were calculated by mMass open source platform.
Keywords: Protein Binding; Cattle; Proteolysis; skot; reagencia zkříženě vázaná; Protein structure design; mapování interakce mezi proteiny; Quantification; sekundární struktura proteinů; Protein Structure, Secondary; Calmodulin; kalmodulin; Protein Interaction Mapping; vazba proteinů; Animals; konformace proteinů; Spectrometry, Mass, Electrospray Ionization; zvířata; Mass spectrometry; hmotnostní spektrometrie s elektrosprejovou ionizací; Cross-Linking Reagents; Protein Conformation; Chemical cross-linking